A comparative analysis between DWT-bitplane slicing algorithm and histogram shape based algorithm for image watermarking - Zacharia, Olivia; George, Nimmy (2017 IEEE International Conference on Circuits and Systems (ICCS), 2017)
The ease of availability of digital data in this digital world has increased their unfair and unjust use which should be tackled with reliable and robust techniques. Digital images can be protected to a large extend with the application of watermarks. A large number of watermarking techniques have been developed during the past few decades and are found to be useful in one or the other way. This paper presents a comparative study between two different digital image watermarking algorithms - one based on Haar DWT and bit-plane slicing and the other is a histogram shape based method where the watermarking is done using an embedded security key. Moreover, the simulation results for the watermarking algorithm based on Haar DWT and bit-plane slicing using Xilinx ISE Design Suite are also used for comparison. Comparison is done mainly on the basis of Peak Signal to Noise Ratio and Mean Signal Error values for the images.